Nomenclatural problems associated with the generic names Obisium Leach, 1814, Blothrus Schiödte, 1847 and Neobisium Chamberlin, 1930 (Arachnida: Chelonethi) - Judson, Mark L. I. (Zootaxa, 2012)
Obisium Illiger, 1798 (type species Acarus cancroides Linnaeus, 1758) and Obisium Leach, 1814 (type species Chelifer trombidioides Latreille, 1804) are shown to be different nominal taxa and hence homonyms, rather than synonyms. The synonymy between Cheliferidae Westwood, 1838 (type genus Chelifer Geoffroy, 1762) and Obisiidae Sundevall, 1833 (type genus Obisium Leach, 1814) is therefore rejected. Chthonius C.L. Koch, 1843 (type species Obisium orthodactylum Leach, 1817, a junior objective synonym of Chelifer trombidioides Latreille, 1804) is a junior objective synonym of Obisium Leach, 1815. Chthoniidae Daday, 1888 (and coordinate family-group names) would therefore become a junior objective synonym of Obisiidae Sundevall, 1833 (and coordinate taxa), unless action to avoid this is taken by the International Commission on Zoological Nomenclature. Because Neobisium Chamberlin, 1930 was proposed as a replacement name for Obisium Leach, 1814, its type species must also be Chelifer trombidioides, notwithstanding Chamberlin’s (1930) statement that its type was Obisium muscorum Leach, 1817, which means that Neobisiidae Chamberlin, 1930 (and coordinate names) would be a junior objective synonym of Chthoniidae (and coordinate names). In order to avoid these highly disruptive synonymies, it is recommended that the Commission use its plenary powers to designate Obisium muscorum Leach, 1817 as the type species of Obisium Leach, 1815 and hence of Neobisium. The publication date of Blothrus Schiödte, 1847 and Blothrus spelaeum Schiödte, 1847 is clarified.